Cortinarius jiaoheensis (Cortinariaceae), a new species of Cortinarius subgenus Telamonia section Flexipedes, from northeast China - Luo, Ying; Bau, Tolgor (Phytotaxa, 2021)
A new Cortinarius species in subgenus Telamonia section Flexipedes, Cortinarius jiaoheensis, is described based on morphological characteristics and molecular data. It is characterized by small basidiomata, with the surface of the pileus completely covered by woolly squamules, and ellipsoid to obovoid ellipsoid basidiospores. This species produces basidiomata in the autumn and is currently known only from northeast China.